Taking exception: Christopher Phelps challenges Jefferson Cowie’s The great exception - Phelps, Christopher; Cowie, Jefferson (Duke University Press, 2017)
A "Point/Counterpoint" interview of historian Jefferson Cowie with deliberately provocative thesis-testing questions.